2016
DOI: 10.1590/1807-1929/agriambi.v20n9p800-805
|View full text |Cite
|
Sign up to set email alerts
|

Mini tomato production in organic system under greenhouse with partial control of meteorological elements

Abstract: A B S T R A C TThe objective of this research was to evaluate the meteorological elements of the environments and the production components of mini tomato crop in organic system in different forms of cultivation, biofertilizer doses and technological levels of protected environments. The research was conducted in completely randomized design in a 3 x 2 x 5 factorial scheme, corresponding to three greenhouses (A -climatized, B -mobile screen and C -fixed screen), two forms of cultivation (pots and beds) and fiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…The application of continuous liquid composting manufactured using Microgeo ® biofertilizer in soil did not increase the yield of organic mini tomato crop (Araujo et al, 2016). According to Araujo et al (2016) the lack of significance of the biofertilizer may be related to the amount of organic matter present in the soil and addition of bovine manure and organic fertilizer, which mineralized, masking the effects of the biofertilizer. Mesquita et al (2014) reported that the commercial biofertilizer Microgeo ® did not cause qualitative or yield benefits for two melon cultivars.…”
Section: Rice Yieldmentioning
confidence: 99%
See 1 more Smart Citation
“…The application of continuous liquid composting manufactured using Microgeo ® biofertilizer in soil did not increase the yield of organic mini tomato crop (Araujo et al, 2016). According to Araujo et al (2016) the lack of significance of the biofertilizer may be related to the amount of organic matter present in the soil and addition of bovine manure and organic fertilizer, which mineralized, masking the effects of the biofertilizer. Mesquita et al (2014) reported that the commercial biofertilizer Microgeo ® did not cause qualitative or yield benefits for two melon cultivars.…”
Section: Rice Yieldmentioning
confidence: 99%
“…Moreover, the biofertilizer application improves the soil physical properties (Galbiatti et al, 1996). The biofertilizer features described above sustain the fact that it can help increasing the yield of crops, although some researches are controversial (Mesquita et al, 2014;Aparecido et al, 2017;Kumar et al, 2014;Araujo et al, 2016). It should also be noted that biofertilizers are much more economically attractive than conventional chemical fertilizers (Freitas et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…The increased interest of consumers makes the cultivation of mini tomatoes an attractive option. However, in addition to the lack of cultural management research (Maciel et al, 2016), the cultivation predominates in greenhouse conditions (Araújo et al, 2016;Candian et al, 2017), which needs more initial investments.…”
Section: Introductionmentioning
confidence: 99%
“…In 2018, the cultivated area was 41,336 ha with a yield of 19 t ha -1 (SIAP, 2018). This yield is considered low due to inefficient water management (LÓPEZ-LÓPEZ et al, 2008), environmental factors and pests and diseases (SANTIAGUILLO-HERNÁNDEZ et al, 2009), and because there is a lack of research in protected production agriculture systems (REIS et al, 2013;PEÑA-LOMELÍ et al, 2014;ARAUJO et al, 2016). There are also few studies on plant densities among other determining factors, that could possible increase yield and obtain the potential yield of 83.8 t ha -1 mentioned by SOLDEVILLA-CANALES et al (2002) for this crop.…”
Section: Introductionmentioning
confidence: 99%